Analysis of West Java Swimming Athletes' Performance in Breaststroke - Irfan Apriliana; Dede Rohmat Nurjaya; Gafur Ammar Santoso; Mulyana (Universitas Negeri Semarang, 2025)
This research aims to analyze the performance of West Java swimming athletes in the 100-meter breaststroke event. This analysis is crucial given the importance of race analysis in competitive swimming and the limited specific studies on the breaststroke at the regional level. Employing a descriptive quantitative approach, performance data from eight athletes (four male and four female) from the West Java Swimming Series 2025 were analyzed. The parameters measured included stroke count, stroke rate, stroke length, time per 10-meter segment, total race time, and speed per segment. The results indicate that DE (male) and AL (female) were the fastest overall swimmers. AL, in particular, demonstrated highly competitive performance, even outperforming several male swimmers. Analysis of split times revealed a progressive deceleration pattern from segment 1 to segment 4 in most athletes due to fatigue. However, DE and AL consistently maintained their speed in the final segments. In terms of stroke count, there was a tendency for an increase from SC 1 to SC 4, while the highest stroke rate was observed in SR 4. For stroke length, SL 1 had the highest average, and Velocity 1 recorded the highest average among the speed segments. Standard deviations indicated better performance consistency among male swimmers compared to female swimmers.